MODEL PENERIMAAN DAN PENGGUNAAN PROGRAM APLIKASI MICROSOFT OFFICE BAGI SISWA SMK PANCAKARYA TANGERANG DENGAN METODE UTAUT - . Syarifudin (LPPM Universitas Bina Sarana Informatika, 2014)
UTAUT suggests that the intention to behave is influenced by people's perceptions of the performance expectancy, effort expectancy, and social influence, And the behavior to use a technology is influenced by the perception of the people towards the intention to behave and help conditions. The study was moderated by sex (gender), classes, and majors. Data analysis was performed with the approach of Structural Equation Modeling (SEM) is a covariance-based SEM AMOS 18 program. From the results of SEM analysis found that the model did not fit. Therefore, use diagram analysis. Based on the results of data analysis has been done, it is concluded that the behavior of the acceptance and use of Microsoft Office Applications Program students are affected by social influences (social influence) and the presence of facilities that support (facilitating condition) and there are differences moderating variables subject to the acceptance and use of the Program Application Microsoft Office.